Severe panuveitis in neuro-Behçet’s disease in Malaysia: a case series - Khairuddin, Othman; Ahmad Tajudin, Liza Sharmini; Mohtar, Ibrahim; John, Tharakan; Ryoji, Yanai; Embong, Zunaina (Dove Medical Press, 2017)
Behçet’s disease (BD) is a multisystemic disease that is very rare in Malaysia. About 5% of patients develop central nervous system involvement, termed neuro-Behçet’s. Neuro- Behçet’s is one of the most serious causes of long-term morbidity and mortality. We report two cases of neuro-Behçet’s associated with uveitis (ocular BD) highlighting the clinical presentation, diagnostic measurement, and therapeutic management of these cases.